Silence in Digital Communication: A Case Study of Ganjar Pranowo’s Speech on YouTube - Indrya Mulyaningsih; Arifin Nasa; Reza Muamar Zaki (Jurnal Gramatika, 2024)
This research aims to analyze the types and functions of silence in Ganjar Pranowo's speech on the Becoming Human YouTube channel, focusing on the role of silence in digital communication. This research uses a qualitative descriptive approach to identify two main types of silence: quiet and filled. The research results show that intentional silence is used for several pragmatic purposes, including regulating breathing, providing emphasis, segmenting grammatical units, and conveying emotional expressions. In contrast, unintentional silence occurs due to the speaker's mental processes in planning and producing speech, such as careful word selection and spontaneous correction of speech errors. This research has important implications for Indonesian language learning, especially speaking and listening skills. Understanding the use of comfort can help students organize the flow of communication and reduce the stress of public speaking. Additionally, silence can be taught as an effective communication strategy in professional and digital contexts.